Movement variability during the flight phase in a single Back Sideflip (Wildcat) in snowboarding - Bacik, B.; Kurpas, W.; Marszalek, W.; Wodarski, P.; Sobota, G.; Starzynski, M.; Gzik, M. (Journal of Human Kinetics, 2020)
Understanding the structure and variability of motion is essential for sports technique development and an effective training design. Biomechanical analysis is particularly important in new disciplines with spatially complex motions, such as snowboarding. This study aimed to evaluate the level of variability of the kinematic variables in a single backside snowboard flip known as a "wildcat". Forty-six correct flips performed by 7 experienced athletes (age: 24.9 ± 4.34 year; body mass: 71.6 ± 12.87 kg; body height: 177.4 ± 6.99 cm) were recorded using an optoelectronic VICON system in the controlled setting of an indoor freestyle park. Athletes were equipped with special boards with wheels and the geometry of the ramps corresponded to the actual on-snow conditions. The analysis revealed two distinct single flip strategies, which differed in the way the tuck position was sustained. For all the measured variables, the coefficient of variation was computed, which allowed to identify the athlete with the highest (average 45.3%) and lowest (average 20.5%) variability of kinematic variables. Moreover, it was shown that the lowest values of the coefficient of variation occurred at the end of the grouping phase (average 14%) and that among all the different variables, those related to the duration of motion were most unstable (average 63%, SD = 48.5%).